Winners' Consent? Citizen Commitment to Democracy When Illiberal Candidates Win Elections. Issue 2 (14th January 2022) - Cohen, Mollie J.; Smith, Amy Erica; Moseley, Mason W.; Layton, Matthew L.
Abstract: Democracy is in decline worldwide, primarily because voters elect candidates harboring antidemocratic aspirations. Scholars argue that elections animate the democratic spirits of winners and deflate those of losers, but what about contests ending in the victory of authoritarian candidates? To answer this question, we consider the dynamics of commitment to democracy in Brazil's 2018 presidential campaign. Drawing on AmericasBarometer data and an original five‐wave panel survey, we confirm that Jair Bolsonaro's campaign attracted skeptics of democracy. Although his election and inauguration boosted his supporters' allegiance to the political system, it also exacerbated their tolerance for institutional ruptures such as executive‐led coups. Meanwhile, election losers retained their democratic commitments. As a result, the authoritarian victory narrowed preexisting winner–loser gaps in support for the political system, but widened gaps in tolerance for certain antidemocratic maneuvers. Thus, authoritarian electoral victories can foster short‐term satisfaction among democracy's critics while abetting future instability.